2001
DOI: 10.1054/bjoc.2001.1799
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer incidence in a cohort of twin babies

Abstract: We studied childhood cancer incidence in a population-based twin cohort using record linkage to the National Registry of Childhood Tumours. After correcting for mortality, an incidence deficit was observed (Standardized Incidence Ratio (SIR) 79; 95% Confidence Interval (CI) 39–120). Pooled analysis with data from published cohort studies indicates a similar significant incidence reduction (SIR 81, 95% CI 67–96). Further studies are warranted. © 2001 Cancer Research Campaign http://www.bjcancer.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…However, previous studies have suggested that twins had lower risk for cancers of the lung (20, 48, 49), skin (20), colon, and rectum (18, 20, 48). Thus, it does not seem likely that the average lower birth weight and gestational age for twins (50, 51) compared with singletons influence cancer risk, which has also been supported in previous studies (5254). …”
Section: Discussionsupporting
confidence: 72%
“…However, previous studies have suggested that twins had lower risk for cancers of the lung (20, 48, 49), skin (20), colon, and rectum (18, 20, 48). Thus, it does not seem likely that the average lower birth weight and gestational age for twins (50, 51) compared with singletons influence cancer risk, which has also been supported in previous studies (5254). …”
Section: Discussionsupporting
confidence: 72%
“…One study assessed whether cancer occurred more often in the heavier twin, which was the case for leukemia but not all other cancer types combined (5, 9). Another found that there was a reduced incidence of childhood cancer overall in twins weighing below 3000g at birth and an excess in twins weighing 3000g or more (7). Among the few studies that have examined specific cancer diagnoses besides leukemia, one reported fewer cases of renal cancer than expected (4).…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that being a twin is protective for childhood cancer, possibly due to the lower birth weight of twins, earlier limitation of their growth velocity, or the selection effects of higher intrauterine death rates (Murphy et al, 2001;Neale et al, 2005;Milne et al, 2007). It is not yet known how far this extends into young adulthood, although it seems likely that there is no long-term difference in the overall risk of cancer in twins compared with singletons (Hemminki and Chen, 2005).…”
Section: Discussionmentioning
confidence: 99%